GOVERNMENT AND PRIVATE COLLABORATION IN HANDLING COVID-19 PANDEMIC IN SLEMAN DISTRICT - Febty, Inggi Miya; Sakir, Sakir; Mutiarin, Dyah; Rahmawati, DE (Universitas Negeri Yogyakarta, 2021)
The research question is how the district government collaborates through the task force, MCCC and volunteers in handling the COVID-19 pandemic in Sleman Regency. This research aims to describe and analyze the collaboration of the Regency government through the task force, MCCC in handling the COVID-19 pandemic in Sleman Regency; to describe and analyze supporting and inhibiting factors in collaboration between district governments through the task force, MCCC and volunteers in handling the COVID-19 pandemic in Sleman Regency. This type of research is a type of qualitative research with a case study design that will describe and analyze the collaboration of the Regency government through a task force, MCCC and volunteers in handling the COVID-19 pandemic in Sleman Regency. The data collection methods used were interviews and documentation. The data analysis technique used qualitative data analysis. The results of this study can be concluded that the government and Muhammadiyah as private parties have established relationships and resulted in collaboration. The existence of the COVID-19 pandemic has made the government form a special team to deal with the pandemic, namely the task force, the COVID 19 program created by the Task Force to coordinate with the central government and private elements. For the government, MCCC is a partner in capturing aspirations, while for MCCC the government is a means of realizing aspirations in a broader context.